How To Increase Purchase Intention To Hello Baby Product - Wahyu Pratama Teja; Liliana Dewi (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
The rate of population growth in Indonesia is still relatively high. This is evidenced by Indonesia being the fifth largest donor of birth number in the world. The birth rate in Indonesia is projected from 2015 to 2042 on average 4 million children birth annually. Provide opportunities to the company Hello Baby to produce baby goods and sell to consumers. Sales of Hello Baby products are strongly influenced by consumer buying interest in Hello Baby products. The level of interest in buying a product reflects the marketing success of the company that produces the product. Research aims to determine the impact of price and quality of products on buying interest. The number of samples in this study was as much as 188 people counted with the Slovin formula. The type of data used is the primary data that is collected by spreading the questionnaire to the respondent. Data analysis using multiple linear regression analyses. The results showed that prices positively and significantly affect the interest in buying consumers of Hello Baby. It means the better and more attractive the price offered, the higher the interest in buying consumers Hello Baby. Product quality affects positively and significantly on the interest in buying Hello Baby consumers. This means that the better the quality of the product, the higher the consumer's buying interest in Hello Baby.